REORIENTASI STRATEGI PEMBELAJARAN PENDIDIKAN ISLAM BERBASIS REKONSTRUKSIONALISME DI ERA DISRUPSI DIGITAL - abdul hayyi; Noor Malihah; Ferli Septi Irwansyah; Hamsir; Yosi Huzna Nidia Ningrum (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2026)
The rapid development of digital technology has changed the orientation, methods, and learning culture of Islamic education. This article aims to analyze the reorientation of Islamic education learning strategies based on reconstructionism in the era of digital disruption. This study uses a library research method by examining books, journal articles, and relevant academic documents related to reconstructionism, Islamic education, digital transformation, and learning strategies. The data were analyzed through thematic identification, conceptual interpretation, and critical synthesis. The findings indicate that reconstructionism offers an important perspective because it views education as an instrument for rebuilding social, moral, and cultural life. In the context of digital disruption, Islamic education learning strategies need to move from conventional, teacher-centered, and memorization-oriented approaches toward reflective, dialogical, contextual, collaborative, and value-based digital learning. This article emphasizes that Islamic education should integrate Islamic values, digital literacy, critical thinking, social awareness, and ethical use of technology. Therefore, reconstructionism can serve as a conceptual foundation for developing Islamic education that is adaptive, transformative, and relevant to contemporary educational challenges.